Digital Islamic Banking and Millennial Preferences: A Systematic Literature Review - Mardiantoro; Wargo; Kurniawan; Anshori (Zabags Qu Publish, 2025)
This article examines millennial behavioral patterns in adopting Islamic digital banking services using the Theory of Planned Behavior (TPB) as the primary analytical framework. The study was conducted through a systematic literature review of empirical works published in reputable journals over the last five years, focusing on key factors influencing behavioral intention and actual usage. Data sources were drawn from international open-access databases, applying rigorous inclusion and exclusion criteria to ensure relevance and quality. The review findings highlight that perceived usefulness, perceived ease of use, religiosity, and trust in Shariah compliance consistently emerge as dominant determinants. Moreover, social influences formed through peer groups and digital communities were found to strengthen the adoption process, especially in the millennial segment that is highly exposed to technology. These results underline the significance of integrating technological innovation with religious values to enhance user acceptance. The article contributes to the theoretical enrichment of TPB in the Islamic financial context while offering practical insights for financial institutions and policymakers to design digital banking strategies that are user-oriented, ethically grounded, and responsive to millennial digital behavior.